Examining mental health literacy, help-seeking behaviours, distress, and wellbeing in UK coaches. (August 2020) - Gorczynski, Paul; Gibson, Kass; Clarke, Nathan; Mensah, Tyrone; Summers, Rory
Although research has explored stress in coaches, little is known about their mental health literacy and how this is associated with their mental health. Their mental health literacy may have an impact on the wellbeing of their young players. This study examined levels of mental health literacy, help-seeking behaviours, distress, and wellbeing, as well as relationships amongst these variables, in coaches in the United Kingdom. Coaches were recruited through social media and asked to fill out questionnaires. A total of 103 coaches ( n = 65 men, n = 37 women, n = 1 other gender) participated in the study. Coaches had an average age of 27.9 (SD = 10.6) years. Most self-identified as heterosexual ( n = 85, 82.5%), had four or more years of experience ( n = 46, 44.7%), coached children ( n = 77, 74.8%), and coached at either the beginner ( n = 30, 29.1%) or amateur levels ( n = 66, 64.1%). In total, 20 (19.4%) coaches indicated a previous diagnosis of a mental disorder. A total of 51 (49.5%) coaches indicated that, at the time of the completion of the survey, they exhibited symptoms of a mental disorder. Overall, the average mental health literacy score was 123.10 and lower than in previous studies. Mental health literacy was not significantly associated with help-seeking behaviour, distress, or wellbeing. General help-seeking behaviour was positively correlated with wellbeing. The results suggest that coach certification programmes could adopt strategies to help coaches improve their knowledge of mental health services and how such services may be accessed. These changes may improve the wellbeing of coaches and may benefit their athletes.